Content analysis of Biology for Philippine high schools the relationships of living things, textbook and laboratory, manual - Cruz, Azucena G. (s.n.], 1974)
This is a content analysis of the UPSEC Biology for Philippine High Schools: The Relationship of Living Things textbook and laboratory manual. This focuses on four aspects, namely: (1) the index of student involvement (2) word loading (3) index of spread of the 10 most frequently-appearing technical and nontechnical terms and the non-applicability of the formula for determining the index of spread in correlating the index value to the different factors affecting the index of spread; and (4) rate of introduction of technical terms.